Pengaruh Pajak Daerah Dan Dana Alokasi Umum (DAU) Terhadap Tingkat Kemandirian Keuangan Daerah - Dela Yulia; Dirvi Surya Abbas; Ahmad Jayanih (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The porpuse of this study was to determine the effect of regional taxes, regional levies, and general allocation funds on the level of regional financial independence in regency and city governments in Banten Province. The research period used is 4 years, namely 2018 – 2022. The study population is all districts and cities in the Povinsi Banten region. The sampling technique was Non Probability Sampling. The type of data used is secondary data obtained from the website of the Directorate General of Financial Balance. The analysis method used is panel data regression analysis. The results showed that regional taxes had a significant positive effect on the level of regional financial independence, regional levies had a negative effect on the level of regional financial independence, and the general allocation fund had a negative and insignificant effect on the level of regional financial independence.